Basophils in immune responses against helminths. - Vöhringer, David (Microbes and Infection, 2011)
Basophils are a major source of IL-4 and IL-13, two key cytokines that orchestrate expulsion of gastrointestinal nematodes in different mouse models. Based on recent reports, this review discusses potential roles of basophils and other cells during early and late phases of the immune response against parasitic worms. © 2011 Institut Pasteur.
UnivIS-Import:2015-03-09:Pub.2011.med.IKMI.pifto.basoph_3
Keywords: Basophils; Helminths; IL-4/IL-13; Th2 cells